Multi-hierarchical nanoparticles with tunable core by emulsion polymerization processes - Udabe, Jakes (2023)
Nanoparticles (NPs) with functional cores are gaining research interest due to their advanced architecture. However, exposed reactive groups on NP surfaces can lead to material side reactions and biomedical tissue damage. NPs with multi-hierarchical morphologies can be synthesized by various methods; however, controlling the size and position of the functional groups using conventional and scalable methods is still a challenge. This study explores emulsion-based polymerization methods for producing multi-hierarchical NPs with varying sizes and compositions. We compared micro-, macro-, and semi-batch emulsion polymerization using 2-hydroxyethyl methacrylate (HEMA) and pentafluorophenyl methacrylate (PFMA) as co-monomers. The components present in PFMA can be substituted and are used for post-synthetic functionalization. The results suggest that the architecture of the synthesized NPs is multi-hierarchical, with the substitutable pentafluorophenyl units surrounded by HEMA monomers. Additionally, we evaluated the NPs' ability to enhance dermal drug penetration using nile red as a hydrophobic drug model. Significant variations in skin permeation enhancement properties were observed among the NPs, underscoring the impact of the synthesis method on nanocarriers' drug delivery performance.